Quantum thermodynamics : quantum szilard engine powered by quantum coherence - Gan, Beng Yee (Nanyang Technological University, 2020)
Traditional thermodynamics assumes that physical systems live in a probabilistic mixture of energy eigenstates, such that any lack of knowledge of each system’s definite energy is due to classical uncertainty. However, quantum mechanics enables systems to be a quantum superposition of eigenstates, and moreover, to have these superpositions be correlated non-locally across bipartite systems. A theoretical model is developed to study the thermodynamic properties of such systems, using a combination of quantum analogues of thermal operations and Maxwell’s demon. In this thesis, we demonstrate that using a sufficient number of superposition states, the non-local correlation with a two-level battery qubit can be established perfectly regardless of the amount of coherence stored in the superposition states. Here, each of the superposition states operationally functions as an ancilla that enhances the distillation process. Moreover, the battery qubit can be fully charged by utilizing the huge energy degenerated-subspaces formed by many copies of superposition states. The free energy stored in the battery qubit, that originates from the quantum coherence, is extracted as work which quantified using information-theoretic measures giving the operational value to quantum coherence.